Becoming-Other: (Dis)Embodiments of Race in Anne Rice’s Tale of the Body Thief - Holmes, Trevor (Romanticism on the Net, 2006)
AbstractThe vampire/human split in Anne Rice's Vampire Chronicles is structured like a racial split. Becoming a vampire constitutes an essence, a shared material difference that is not something humans can come close to understanding. In the process of erasing actual racial differences through the "Dark Gift," Rice relies on embodiments of ethnicity and racial specificity in her management of gay male desire (a major factor in her popularity). The complexity of the relationships that shift and multiply between desire, race, sexuality and otherness is captured most strikingly in the fourth novel of the series, Tale of the Body Thief. After establishing the gender and sexuality work accomplished by Lestat’s body-switching, the paper examines David Talbot's switch into a young male body himself. Talbot’s own becoming-other, and becoming-vampire thereafter, are instances of both general and specific racialized embodiment. Lestat's experience of the human flesh is different from Talbot's, and in fact does more to constitute identity as gender and sexuality than as race. Talbot's assimilation into Lestat's identity formation (erasing ethnicity by way of becoming an other) still produces a specificity, one that exoticizes a youthful otherness overcoded by Portugal, Africa, India and Brazil. However, the othered body can only be animated by an aging white British gentleman’s mind and manners.